Rancangan Buku Saku Keanekaragaman Serangga Permukaan Tanah Di Hutan Larangan Adat Kenegerian Rumbio - Jannah, Miftahul; Suwnodo, Suwnodo; Nursal, Nursal (Peneliti.net, 2025)
This study aims to determine the diversity of ground surface insect species in the Kenegerian Rumbio Customary Prohibition Forest, then the results of the study were integrated into a pocket book to determine the validity of the pocket book of Ground Surface insect diversity in the Kenegerian Rumbio Customary Prohibition Forest. This research has 2 stages, namely; the first stage of collecting information on ground surface insects in the Kenegerian Rumbio Customary Prohibition Forest area, using the survey method. And the second stage is the utilization of survey results for pocket book making, using R&D research design with the ADDIE model. Based on the results of research conducted in the Kenegrian Rumbio Customary Prohibition Forest, conclusions can be drawn, namely: The diversity of ground surface insects in the Kenegrian Rumbio Customary Prohibition Forest was found as many as 5 orders, namely the order Blattodea, coleoptera, hemiptera, hymenoptera and orthoptera, consisting of 21 species with a total of 2,136 individuals. The species diversity index at the shaded station is 2.012. At semi-shaded stations with an index of 1.880 and open stations 1.821. At each research station in the Kenegerian Rumbio Indigenous Prohibition Forest, the diversity of soil surface insects is classified in the medium category. The design of the pocket book of soil surface insect diversity in the Kenegrian Rumbio Customary Prohibition Forest is very valid and can be used in class X high school biodiversity material.